Regional policy and cooperation framework on local governance and local democracy in the Caribbean ([s.n.] [S.l.], 2008)
Addresses issues relating to local governance and local democracy in CARICOM member states. Includes issues such a major principle of local governance and the current status and realities of local government in the Caribbean.
Keywords: GOVERNANCE